2012
DOI: 10.1007/s10995-012-1068-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-Disaster Reproductive Health Outcomes

Abstract: We examined methodological issues in studies of disaster-related effects on reproductive health outcomes and fertility among women of reproductive age and infants in the United States (US). We conducted a systematic literature review of 1,635 articles and reports published in peer-reviewed journals or by the government from January 1981 through December 2010. We classified the studies using three exposure types: (1) physical exposure to toxicants; (2) psychological trauma; and (3) general exposure to disaster.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 31 publications
3
39
0
1
Order By: Relevance
“…[15] Researchers believed that the presence of some indicators such as accessible prenatal care, accessible contraceptive methods, and breastfeeding in affected areas can help health care professionals in identifying and fulfilling reproductive health needs of women. [13] These enable health care professionals to decrease the impacts of natural disasters through some basic measures.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Researchers believed that the presence of some indicators such as accessible prenatal care, accessible contraceptive methods, and breastfeeding in affected areas can help health care professionals in identifying and fulfilling reproductive health needs of women. [13] These enable health care professionals to decrease the impacts of natural disasters through some basic measures.…”
Section: Introductionmentioning
confidence: 99%
“…Little to no surveillance is conducted among this vulnerable population. 11,12 This may be due to pregnant women making up just 1% of the general population and 5% of women of reproductive age at a given point in time in the United States, making it difficult to conduct population-based surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to postdisaster reproductive outcomes, it is unclear which of these proximate sources of hurricane-induced distress exercises the greatest influence over fetal outcomes. Zotti et al 23 maintain that improved public health surveillance can resolve such questions, advancing understanding of exposure effects on maternal risk factors, behaviours and fetal outcomes. Specifically, they suggest appending a disaster-specific module to the Pregnancy Risk Assessment Monitoring System (PRAMS), a population-based surveillance survey collecting vital information on maternal and child health before, during and after pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…While postdisaster negative effects on fetal health are partly explained by compromised maternal access to healthcare before and after a hurricane event,21 22 researchers postulate that disaster-induced trauma and distress experienced by pregnant mothers may impair the development of an unborn child 23. Observational studies have found associations between maternal stress and newborn health 24–29.…”
mentioning
confidence: 99%
See 1 more Smart Citation